Effect of speed on flow and enjoyment for driving and rollercoasters. (February 2022) - Stephens, Richard; Smith, Maddie
Highlights: Psychological flow is achieved when situational challenge is matched to personal skill. We theorised that driver speed choice is influenced by flow seeking. Supporting our theory, flow and enjoyment ratings were increased at faster speeds. Promoting flow via means independent of speed may help reduce speeding behaviour. Abstract: Worldwide, road traffic injuries are the eighth highest cause of death, and campaigns targeting excessive speed are a common approach to tackling this issue. Yet one element missing from these campaigns is acknowledgment that speed is inherently enjoyable. This study of UK road users was designed to assess whether flow theory predicts the enjoyment of the sensation of speed in the contexts of road driving and riding a rollercoaster. In a repeated measures experimental design, participants viewed 5 first-person videos from a car-driver perspective under the conditions: congested traffic, 20 mph, 25 mph, 30 mph, 35 mph. As a counterpoint to road driving, comprising an experience designed for enjoyment of rapid speed, they also viewed 3 rollercoaster videos under the conditions: 0.5x normal speed, normal speed and 1.5x normal speed. Participants rated experience of flow and enjoyment after each video. Flow and enjoyment ratings were increased at faster speeds compared with slower speeds for the road and rollercoaster contexts. Sensation seeking moderated flow scores for road driving such that higher sensation seekers rated higher levels of flow at 20–35 mph, but not in congestion, compared with lower sensation seekers. Findings are consistent with a flow explanation of speeding, such that increased speed leads to increased flow experience. Sensation seekers may be more prone to such motivation to speed, although further research is needed to verify this. We recommend for enjoyment and flow to be considered in anti-speeding campaigns and for driving to be re-designed to facilitate flow at slower speeds.